Biometric Technologies, Electoral Fraud and the Management of Elections in Nigeria and Zimbabwe (The Strategic Review for Southern Africa, 2020)
The introduction of biometric technologies (BT) in Africa’s developing democracies has raised concerns on the BT effect on voter turnout and voter confidence. Questions have also been raised about BT effectiveness as an anti-rigging and anti-fraud solution that would ensure credible elections. Through secondary and survey data, the study used Nigeria and Zimbabwe in Africa as units of analysis, as both countries have similar historical trajectory and conditions like weak institutions, reliance on international donors and the use of BT. The study discovered that at the pre-election stage, BT use enhanced election credibility as evidenced in computerized voter register and Smart Card Readers (SCR). It also discovered that at the election stage, biometric technologies served as an effective anti-rigging measure by eliminating cases of unregistered voting, ballot stuffing and multiple voting. The study further shows that the application of biometric technologies affects voters’ confidence and turn out negatively. For instance, the more biometric technologies (BM) are deployed and used in Nigeria and Zimbabwe, the modest the level of voters’ turnout (43.65% in 2015 elections and 52% 2000 elections respectively), showing the limitations of BT in resolving issues of voters’ confidence, turnout and electoral fraud in Nigeria and Zimbabwe.
Keywords: Biometric Technology; Elections: Fraud; Election Management; Nigeria; Zimbabwe